2017
DOI: 10.1021/acs.jctc.7b00226
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Dynamics of Propeller Loops in Human Telomeric DNA Quadruplexes Using Atomistic Simulations

Abstract: We have carried out a series of extended unbiased molecular dynamics (MD) simulations (up to 10 μs long, ∼162 μs in total) complemented by replica-exchange with the collective variable tempering (RECT) approach for several human telomeric DNA G-quadruplex (GQ) topologies with TTA propeller loops. We used different AMBER DNA force-field variants and also processed simulations by Markov State Model (MSM) analysis. The slow conformational transitions in the propeller loops took place on a scale of a few μs, empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 126 publications
(326 reference statements)
2
83
0
Order By: Relevance
“…29 In the present case we observe perturbation of GQ core of an experimentally determined structure, which is exceptionally rare in AMBER GQ simulations. [68][69][70][71][72]…”
Section: Dimer Of Dna Gqs Is Stable In Simulations (Simulations 1a -1e)mentioning
confidence: 99%
See 1 more Smart Citation
“…29 In the present case we observe perturbation of GQ core of an experimentally determined structure, which is exceptionally rare in AMBER GQ simulations. [68][69][70][71][72]…”
Section: Dimer Of Dna Gqs Is Stable In Simulations (Simulations 1a -1e)mentioning
confidence: 99%
“…As for the simulations of the complete 2N3M structure, Na + ions were more dynamic than K + ( Figure S4). 29,[68][69][70]73 In the Simulation 3a, three Na + ion exchange events were observed from 440 ns -2.28 μ s ( Figure S4a). These ion exchanges were linked to the entry of cation from the bottom quartet concurrent with a concerted movement leading to the escape of ion from the top quartet.…”
Section: The Linker Is Not Required For the Stability Of Gq Dimer (Simentioning
confidence: 99%
“…78 A subsequent report by Sponer group to study loop conformations in parallel-stranded quadruplexes highlighted the limitations of these force fields to accurately reproduce experimental structure in all these force field versions. 81 However, it is worth mentioning that modifications of the AMBER force field to bsc0, bsc1 and OL15 were developed to improve the accuracy of simulating double-stranded DNA. 74 In spite of their limitations, these force fields have helped in improving the reliability to simulate quadruplexes.…”
Section: Current Force Fieldsmentioning
confidence: 99%
“…Long timescale MD simulations of quadruplexes have shown that quadruplexes are transitionally stabilised on a shorter timescales and are far from equilibrium states. 76,81 A fully converged system requires extended sampling of the quadruplex-ligand systems. 76,81 A good example is the MD simulation used to study the interactions of tetra-substituted naphthalene diimide compound MM41 and quadruplexes formed in the gene promoter sequences, employing parmbsc0 force field supplemented with χ OL4 modifications.…”
Section: Automated Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation